A Reply to Louis P. Pojman’s Article "The Case Against Affirmative Action" - Maurya, Sooraj Kumar (Conatus - Journal of Philosophy, 2020)
Affirmative action is a public policy purposed to compensate the victims of injustice at the cost of priviledged groups; hence to some it appears as opposing the notion of equality and being against human dignity. Thinkers like Leslie Pickering Francis and John Rawls, on the other hand, argue that affirmative action policies should be implemented for the sake of the oppressed and under-represented groups. Louis P. Pojman in his article “The Case Against Affirmative Action” sets forth nine arguments against strong affirmative action. This paper sets out to challenge Pojman’s arguments one by one, and prove the author’s thesis in support of strong affirmative action.